Features In Edublog That Could Enhance Students Engagement In Learning - Hamdan, Harim Izzati (2011)
The study had been carried out to investigate features in Edublog that could enhance students engagement in learning. Therefore, the study had also been conducted to explore Edublog usage in education and to provide future researchers with valid findings on this area of research. Each Edublog feature had been investigated to gain perspective on its function as well as investigating students level of engagement when using Edublog based on related educational theories.